A mixed methods exploratory study tackling smoking during pregnancy in an urban Aboriginal and Torres Strait Islander primary health care service - Deborah A. Askew; Jillian Guy; Vivian Lyall; Sonya Egert; Lynne Rogers; Leigh-anne Pokino; Peggy Manton-Williams; Philip J. Schluter (BMC, 2019)
Abstract Background Pregnancy can be a time of joy and a time of significant stress. For many Aboriginal and Torres Strait Islander (hereafter, respectfully, Indigenous) women, cigarette smoking, even during pregnancy, is a socially sanctioned behavioural response to stress. Indigenous women smoke during pregnancy at higher rates than their non-Indigenous counterparts. Methods A mixed methods, exploratory study, undertaken in an urban, Indigenous primary health care service, tested the impact and acceptability of a smoking cessation intervention for women pregnant with an Indigenous baby, their significant other (SO), and their primary health care service. The intervention included case management, incentivised smoking cessation support and culturally-based art activities. Results Thirty-one pregnant women and 16 SOs participated. Nearly half attempted to quit at least once during the study, 36% (4/11) of pregnant women had quit at the 3 month assessment and two remained smoke free 1 month postpartum. Most participants self-reported a reduction in tobacco smoking. Exhaled CO confirmed this for SOs (mean reduction − 2.2 ppm/assessment wave, 95% CI: -4.0, − 0.4 ppm/assessment wave, p = 0.015) but not for pregnant women. Many participants experienced social and economic vulnerabilities, including housing and financial insecurity and physical safety concerns. Conclusions Tobacco smoking is normalised and socially sanctioned in Indigenous communities and smoking is frequently a response to the multitude of stressors and challenges that Indigenous people experience on a daily basis. Smoking cessation interventions for pregnant Indigenous women must be cognisant of the realities of their private lives where the smoking occurs, in addition to the impact of the broader societal context. Narrow definitions of success focussing only on smoking cessation ignore the psychological benefit of empowering women and facilitating positive changes in smoking behaviours. Our smoking cessation intervention supported pregnant women and their SOs to manage these stressors and challenges, thereby enabling them to develop a solid foundation from which they could address their smoking. A broad definition of success in this space is required: one that celebrates positive smoking behaviour changes in addition to cessation.